MODERN APPROACHES TO FORMING PROFESSIONAL COMPETENCE OF PRIMARY SCHOOL TEACHERS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
In the context of rapid globalization, digital transformation, and the modernization of education systems, the issue of developing professional competence among primary school teachers has become increasingly significant. This article explores contemporary approaches to shaping teachers’ professional competence, focusing on innovative pedagogical strategies, digital literacy, student-centered methodologies, and continuous professional development. The study highlights the importance of integrating theory with practice, fostering reflective teaching, and adapting to modern educational demands. The findings suggest that a comprehensive and dynamic approach is essential for preparing competent, flexible, and creative primary education professionals.